REVITALISASI PENGETAHUAN LOKAL MELALUI PROGRAM “SENANG MENANAM RAME-RAME” DALAM PENDIDIKAN LINGKUNGAN BERBASIS ETNOPEDAGOGI - Ihda Khairun Nisa; Supriyono; Sri Rahayuningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines how agents of change from Glintung Go Green articulated and transferred ethnopedagogical values to Kampung Semar and how these values can be adapted to environmental learning in primary schools. Using a qualitative descriptive method through interviews, observations, and document analysis, the research identifies that religious principles, local wisdom, and respect for community elders serve as the foundation for transformation. Strategies such as mindset strengthening, musyawarah, storytelling, and studi tiru represent forms of contextual and culturally grounded learning. Communal practices—including daily kerja bakti, Dasawisma-based environmental stewardship, temperature and rainfall monitoring, and waste management through bank sampah and magot cultivation—proved effective in internalizing sustainability values and shifting collective behavior. These practices align with theories of community of practice, experiential learning, and inquiry-based learning. The findings highlight the strong social capital, both internal and external, that supports sustained environmental initiatives and fosters community autonomy. Implications for primary education include adapting ethnopedagogical values into project-based learning, establishing “Dawis Kelas,” integrating simple ecological measurements, developing school waste banks, and building partnerships with green communities or universities. The study concludes that Kampung Semar provides a replicable model of culturally rooted and socially driven environmental education that supports sustainable behavior formation in schools.